INFORMATION CONCERNING BUILDINGS CONSTRUCTION TECHNIQUES OF GETO-DACS IN THE 1ST MILLENNIUM B.C. - Cetean, V. (Bulletin of the Geological Society of Greece, 2004)
Spread according to an amazing plan of defense, at the foot of stately heights, at the blunted peaks or on their oblong ridges, the Dacian fortifications and the villages of some blooming communities are proof of an extraordinary technique of space planning and of setting up of construction works, proved by their variety, richness and monumental character. Raised of large and averagesize limestone blocks, these fortified areas impress not only by the chosen position, by the extraordinary building techniques, in accordance with the most up-to-date principles of strength, equilibrium and waterproofing, but also by iron processing workshops and time measuring devices. This type of buildings implies today, as it did then, specialists in designing, skillful workers for the execution, but more especially experience in construction works. The discovered fortifications and walls totalize at each of the cities about 200,000 m3 of stone, which indicates vast building rock mining, opening-up and rock stripping, splitting of the blocks out of the mother-rock, shaping workshops, efficient ways of transport and an advanced organization of the "building site".